2022
DOI: 10.3390/cancers14174301
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Cognitive Function Evaluations and Interventions for Patients with Brain Metastases in the Radiation Oncology Clinic

Abstract: Brain metastases (BMs) account for a disproportionately high percentage of cancer morbidity and mortality. Historically, studies have focused on improving survival outcomes, and recent radiation oncology clinical trials have incorporated HRQOL and cognitive assessments. We are now equipped with a battery of assessments in the radiation oncology clinic, but there is a lack of consensus regarding how to incorporate them in modern clinical practice. Herein, we present validated assessments for BM patients, curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…Besides, this is to limit confounding factors underlying the acute and early delayed injury likely due to edema with an increase in nerve cell or stromal size [ 61 ]. Notably, during the late-delayed phase, patients tend to experience deficits in memory, spatial relations, visual motor processing, quantitative skills and attention, including somnolence syndromes [ 48 , 62 ]. Interestingly, in the present study, a negative correlation was observed between the neurocognitive tests and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, this is to limit confounding factors underlying the acute and early delayed injury likely due to edema with an increase in nerve cell or stromal size [ 61 ]. Notably, during the late-delayed phase, patients tend to experience deficits in memory, spatial relations, visual motor processing, quantitative skills and attention, including somnolence syndromes [ 48 , 62 ]. Interestingly, in the present study, a negative correlation was observed between the neurocognitive tests and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The two-year survival rate for patients with BM is typically less than 10% 12 . RT, including WBRT and SRS, is one of the essential treatments for BM.…”
Section: Future and Prospectsmentioning
confidence: 99%
“…Common primary tumors associated with BM include lung cancer [5][6][7] , breast cancer [4,8,9] , and malignant melanoma [10,11] . Despite multiple interventions, such as surgery, radiotherapy (RT), and chemotherapy, patients with brain metastases face disappointingly short survival, with a 2-year survival rate that is less than 10% [12] . In recent years, the application of targeted therapy and immunotherapy has led to improvements in survival [4,12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic brain tumors occur in approximately 20% of patients with malignant tumors [ 1 ]. The existence of brain metastases often indicates poor quality of life and survival with a 2 year survival rate of patients with brain metastases less than 10% in general [ 2 ]. The evolving anti-tumor systemic management has improved the survival of patients to a certain degree [ 3 ].…”
Section: Introductionmentioning
confidence: 99%